How does acetonitrile modulate single-walled carbon nanotube diameter during CVD growth?. (May 2019) - Eveleens, Clothilde A.; Irle, Stephan; Page, Alister J.
Abstract: There is a commercial demand for single-walled carbon nanotubes (SWCNTs) with uniform diameters and ( n, m ) chiralities. However, controlling these structural parameters in practice remains a challenge. Recent studies have shown that acetonitrile reversibly modulates SWCNT diameter during chemical vapour deposition (CVD) growth. Here we propose a mechanism to explain this phenomenon using non-equilibrium quantum chemical molecular dynamics simulations. We reveal that acetonitrile-derived radicals actively abstract hydrogen from surface hydrocarbon species as the SWCNT nucleates. This forms hydrogen (iso)-cyanide as a principal chemical product, and decreases the overall surface carbon density during nucleation. By liberating hydrogen, the number of dangling bonds present at the interface of the nucleating carbon structure is increased, which in turn accelerates SWCNT nucleation kinetics. Critically, the number of pentagon rings formed in the SWCNT precursor cap structure increases. Because the nucleation kinetics are much faster than the kinetics of ring defect healing, the pentagons become 'trapped' in the growing SWCNT cap structure, and this leads to more highly-curved SWCNT caps. These more highly-curved caps, combined with the lower surface carbon density and the faster kinetics of nucleation and growth, will ultimately yield narrower-diameter SWCNTs in the presence of acetonitrile. Graphical abstract: Image 1